Topic polyphony of R. W. Emerson’s essay «Self-Reliance» - Khaetskaya, Oksana L. (Journal of the Belarusian State University. Philology, 2019)
On the basis of the topic polyphony analysis of R. W. Emerson’s philosophical essay, peculiarities of his essay prose are revealed. It suggests the principles of mental individualism, the main philosophical world outlook and doctrine about self-reliance by transcendentalism inspirer and founder. The influence of single R. W. Emerson’s beliefs and ideas on consciousness-raising of American nation and those stimulating ethical thought in XIX century in America are revealed.